2014
DOI: 10.1159/000369938
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Impact of Laparoscopic Lymphadenectomy with Preservation of the Left Colic Artery for Advanced Sigmoid and Rectosigmoid Colon Cancer

Abstract: Background: Laparoscopic lymphadenectomy around the inferior mesenteric artery (IMA) with preservation of the left colic artery (LCA) remains a controversial approach. The aim of the study was to investigate the clinical outcomes. Methods: This study analysed 211 patients who underwent laparoscopic resection of advanced (≥T3) sigmoid and rectosigmoid colon cancers with D3 lymphadenectomy including 91 high ligations of the IMA (HL) and 120 low ligations with preservation of the LCA (LL) from January 1998 to Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…In contrast, Fujii S et al [8] found that the level of IMA ligation does not significantly influence the incidence of anastomotic leakage. The total number of harvested LNs and the number of positive LNs show no differences between the two groups, which was similar to the results of previous study [33,34]. Furthermore, previous studies have confirmed that low ligation of IMA in laparoscopic anterior resection for rectal cancer reduces genitourinary dysfunction [35].…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, Fujii S et al [8] found that the level of IMA ligation does not significantly influence the incidence of anastomotic leakage. The total number of harvested LNs and the number of positive LNs show no differences between the two groups, which was similar to the results of previous study [33,34]. Furthermore, previous studies have confirmed that low ligation of IMA in laparoscopic anterior resection for rectal cancer reduces genitourinary dysfunction [35].…”
Section: Discussionsupporting
confidence: 90%
“…Yamamoto et al . further found that low tie with LND in patients with advanced sigmoid and rectal cancer resulted in acceptable outcomes .…”
Section: Discussionmentioning
confidence: 93%
“…Similar studies have been conducted in patients with different tumour stages. [15]. However, regardless of the stage, the metastasis status of the IMA-LNs remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In a comparison of the two groups, preserving the LCA was associated with a larger volume of blood loss. (7,(9)(10)(11)15) were included, involving 961 patients with rectal cancer. A meta-analysis, which applied the fixed-effects model, revealed that there was a significant difference between preservation and non-preservation of the LCA in laparoscopic resection of rectal cancer (RR=-2.28; 95% CI: -3.08, -1.48; P<0.01; Fig.…”
Section: Resultsmentioning
confidence: 99%